Caracterización numérico–experimental del flujo bidimensional alrededor de la sección transversal de una tobera - Muñoz A., Nadia (2009)
This study begins by describing the viscous flow around a body without the influence of 2D free surface and reviewed the fundamental equations of fluids. Then, using the experimental technique LDA, and in the numerical form, the program COMSOL, identified the two-dimensional velocity fields around the cross section of a nozzle at different speeds. Experiments were developed for two models made of wood, one with continuous form and another formed by line segments to determine the influence of the edges. In the back of both models, in the experimental and numerical process, we observe the formation of the wake, characterized by a high variation of axial velocity, which leads to the change in the direction of motion. Besides it notes the influence of free stream velocity on the extent and size of Counterflow area. The pressure distributions obtained in numerical form, show differences between the upper and lower faces of the models, which leads to the conclusion that we will have a net lift force on the section. Finally, the comparison of results was not observed huge variations between flows around Continuous and Segmented sections in the range of speeds tested.